The Influence of Islamic Business Ethics on Criminal Liability: A Transactional Analysis - Dinda Suciana Rambe; Putri Nurlaili (Program Pascasarjana UIN Sumatera Utara Medan, 2023)
This study examines the influence of Islamic business ethics on corporate criminal liability in the context of business law in Indonesia using a normative legal research approach (doctrinal research). The main focus is the principles of muamalah as the foundation of Islamic business ethics that demand justice, trustworthiness, and moral responsibility in corporate activities. This study examines the construction of the element of fault (mens rea) and its relevance in determining corporate criminal liability based on Indonesian positive legal norms. In addition, this study evaluates the application and modification of criminal sanctions in business crime cases that consider the corporation's efforts to comply with or violate muamalah principles. The results of this study are expected to provide a deeper normative understanding of the integration of Islamic ethics in the corporate criminal law system, while also providing recommendations for criminal policy reform that is more responsive to muamalah values.